'Order out of Chaos': Resources, Hazards and the Production of a Tin-Mining Economy in Northern Nigeria in the Early Twentieth Century. (1st August 2012) - Bridge, Gavin; Frederiksen, Tomas
Abstract : This paper examines the development of commercial tin mining in northern Nigeria in the early twentieth century. It recounts how a fundamentally unknown space - an underground zone lying at the edge of Empire - came to be constructed as a mineral rich region, and subsequently integrated with capital and commodity markets in Europe as an extractive economy. From 1902 onwards, the landscape of the Jos Plateau was re-worked to supply tin ores and concentrates to smelters, refineries and fabricators in Europe. At their height, the mines of northern Nigeria provided almost one-tenth of the world's tin. The paper's primary aim is to problematise the processes of ordering and disordering that transformed the Plateau into an extractive economy. To this end, it examines geological science and colonial administration as practices that struggled to differentiate unfamiliar ecologies and invisible geologies into either resources to be exploited or hazards to be overcome. The paper illustrates the economic, political and cultural processes by which some conditions came to be seen as hazards (disease, seasonality of water supply, distance), while others were regarded as resources integral to the commerciality of mining on the Plateau (agricultural labour, land and water courses for sediment disposal, horizontal and vertical variation in ore grades). It shows how commercial exploitation of the Plateau's tin resources radically re-configured both physical landscapes and forms of social organisation on the Plateau, generating novel socio-natural juxtapositions that came to be experienced as poor working conditions, environmental hazards, and conflicts between agriculture and mining over access to land.